Hospital Variation in Early Tracheostomy in the United States: A Population-Based Study*. Issue 8 (August 2016) - Mehta, Anuj B.; Cooke, Colin R.; Wiener, Renda Soylemez; Walkey, Allan J.
Abstract : Objective: Controversy exists regarding perceived benefits of early tracheostomy to facilitate weaning among mechanically ventilated patients, potentially leading to significant practice-pattern variation with implications for outcomes and resource utilization. We sought to determine practice-pattern variation and outcomes associated with tracheostomy timing in the United States. Design: In a retrospective cohort study, we identified mechanically ventilated patients with the most common causes of respiratory failure leading to tracheostomy: pneumonia/sepsis and trauma. "Early tracheostomy" was performed within the first week of mechanical ventilation. We determined between-hospital variation in early tracheostomy utilization and the association of early tracheostomy with patient outcomes using hierarchical regression. Setting: 2012 National Inpatient Sample. Patients: A total of 6, 075 pneumonia/sepsis patients and 12, 030 trauma patients with tracheostomy. Interventions: None. Measurements and Main Results: Trauma patients were twice as likely as pneumonia/sepsis patients to receive early tracheostomy (44.5% vs 21.7%; p < 0.001). Admission to hospitals with higher early tracheostomy-to-total-tracheostomy ratios was associated with increased risk for tracheostomy among mechanically ventilated trauma patients (adjusted odds ratio = 1.04; 95% CI, 1.01–1.07) but not pneumonia/sepsis (adjusted odds ratio =1.00; 95% CI, 0.98–1.02). We observed greater between-hospital variation in early tracheostomy rates among trauma patients (21.9–81.9%) compared with pneumonia/sepsis (14.9–38.3%; p < 0.0001). We found no evidence of improved hospital mortality. Pneumonia/sepsis patients with early tracheostomy had fewer feeding tube procedures and higher odds of discharge home. Conclusion: Early tracheostomy is potentially overused among mechanically ventilated trauma patients, with nearly half of tracheostomies performed within the first week of mechanical ventilation and large unexplained hospital variation, without clear benefits. Future studies are needed to characterize potentially differential benefits for early tracheostomy between disease subgroups and to investigate factors driving hospital variation in tracheostomy timing. Abstract : Supplemental Digital Content is available in the text.